Synthesis, Molecular Docking Studies and Cytotoxic Screening of Novel 2-Substituted Benzimidazole Derivatives - Kankate, Rani S.; Surse, Sunita; Abhang, Pooja; Kakad, Smita; Kshirsagar, Sanjay (International Journal of Membrane Science and Technology, 2023)
Cancer is one of the most serious lifethreatening diseases for which there is presently no cure. According to current World Health Organization (WHO) reports cancer is responsible for one out of every six deaths worldwide. Benzimidazole is a heterocyclic, aromatic molecule that acts as a biological scaffold with anticancer, antitumor, and antiproliferative activities, among other biological effects. benzimidazole and oxazole are the important pharmacophore in the medicinal chemistry, due to their widespread pharmacological activities. So, to exploit their anticancer potential we have selected these two for our research work. So, in order to develop potential anticancer agents, it was considered of interest to synthesize some benzimidazole derivatives. Before synthesis of molecule, Molecular docking was done and afterwards the compound with lowest dock score selected for synthesis. Synthesized derivatives Characterized By Proton Nuclear Magnetic Resonance (1H NMR), Infra-Red (IR), And Mass Spectroscopy (MS) and screen for cytotoxic activity.